Clinical characteristics and predisposing factors of lung metastasis in sacral chordoma: a cross-sectional cohort study of 221 cases - Shi, Qianyu; Guo, Wei; Yu, Siyue; Xu, Jiuhui; Ji, Tao; Tang, Xiaodong (Frontiers in Oncology, 2024)
Introduction Limited studies are available on the topic of lung metastasis in sacral chordoma. The primary objective of this study was to investigate the prevalence, characteristics, associated factors, and prognosis of lung metastasis in sacral chordoma. Methods A total of 221 cases with primary sacral chordoma, all of whom underwent surgical resection at our center, were included in this study. Comprehensive demographic information, imaging findings, and oncological evaluations were collected and thoroughly analyzed. The diagnosis of lung metastasis in the majority of cases was established through radiographic examinations. Results The prevalence of lung metastasis in the cohort was 19.5%, with the lung emerging as the predominant site of distant metastasis. Recurrent chordoma cases exhibited a significantly higher lung metastasis rate in comparison to newly diagnosed chordoma cases (33.33% and 12.76%, p=0.0005). Patients with lung metastasis had a larger tumor size, a higher proportion of previous sacral chordoma surgeries and a greater likelihood of postoperative recurrence. Associated factors of lung metastasis were tumor size, postoperative recurrence and radiotherapy. Patients with lung metastasis exhibited decreased median overall survival (91 vs. 144 months for those without lung metastasis, p<0.05) and recurrence-free survival (27 vs. 68 months, p<0.001) times. Discussion Lung is the most common site of distant metastasis in sacral chordoma with an incidence rate nearly 20%. Larger tumor size and postoperative recurrence are risk factors for lung metastasis while radiotherapy is a protective factor. Occurrence of lung metastasis in sacral chordoma is a negative prognostic factor.